Pharmacogenetics in breast cancer hormone therapy - Supernat, Anna; Wełnicka-Jaśkiewicz, Marzena; Żaczek, Anna (Contemporary Oncology/Współczesna Onkologia, 2010)
Malignant neoplasms are the second leading cause of death in Poland. Breast cancer constitutes 21.5% of all cancer incidence and 13.1% of mortality, which makes it the most common tumour among women. Although new methods of diagnostics and treatment extend the recurrence-free survival and survival rate, it still occurs that a prescribed drug fails to bring satisfactory effects. Pharmacogenetics, the study of genetic variation that gives rise to differing responses to treatment, can help decrease the number of patients who will not benefit from costly therapy due to their genetic predispositions. In the case of hormone therapy administered to breast cancer patients, the most intensively studied genes are: CYP2D6, CYP3A4, CYP3A5, SULT1A1, UGT1A4, UGT2B15 and CYP19. Thus far, a correlation between a particular allele and drug response has been proven only for genes CYP2D6 and CYP19.